A retrospective review on Malaria and Antimalarial drugs in Tripura, India – A Survey Report - Santanu, Mallik; Nilesh, Kumar; Rajesh, Gautam (Indian Journal of Pharmacy Practice)
This study reveals the status of disease malaria in Indian hilly areas with respect to availability of drugs and to identify the common causative parasites of malaria. The work was carried out in urban and rural areas of Tripura. In both cases 500 indoor patients' bed tickets were surveyed to find out the causative parasite, recovery period, antimalarial drug used and again to compare the facilities, diagnostic procedure and clinical status. In this study it was observed that the clinical pharmacy strategies were not well maintained in hospitals of both the areas but the disease was well handled in semi rural areas. The self medication, magic remedies /mantras are still in practice among rural peoples .In this survey it was observed that; in primary cases of malaria, patient recovered within 5-7 days; whereas in severe cases it took 25-30 days, if proper medication is provided. But 25% of patients come to hospital only when disease is in chronic situation. In both the places two types of parasites were mainly found - Plasmodium falciparum & Plasmodium vivax .In acute cases of malaria, chloroquine group of drugs were widely prescribed and in normal cases the proguanil group was the choice of drug by the physicians.
Keywords: Malaria; Anti-malarial drugs; Malaria parasite; Plasmodium